(untitled) (Shiksha Shastra Saurabh, 2025)
Dietary patterns significantly impact on academic performance of children and adolescent, which is a growing area of research. A systematic search of electronic databases was conducted to identify studies examining the association between dietary intake and academic performance. A total 14 studies met the inclusion criteria. The purpose of this systematic review was to identify the dietary patterns and academic performance of children and adolescents as well as its related factors. Data were collected from published articles using a systematic literature review approach. Articles were searched from scholar.google.com, eric.ed.gov, pubmed.com, sematicscholar.com, and Elicit.com using the key words. Out of 120 identified full-text papers, irrelevant articles were excluded. Only English articles focusing on dietary pattern and academic performance were included. The final selection comprised 14 articles. Among them, 21.42% studies were related to healthy home food environment (HFE) and breakfast consumption and remaining 21%, 21%, 14.28%,14.28% and 7.14% were related with processed food and energy dense diet, poverty and life style, Mediterranean diet, balance diet with fruits and vegetables and inflammatory and anti-inflammatory diet respectively. The average age groups of participants in the reviewed studies was 13 years with an age range from 4 to 22 years. The study showed that most studies were cross-sectional (78.57%), followed by longitudinal (14.28%), and systematic review (7.14%). The findings suggest a positive association between dietary intake and academic outcome. The study concluded that dietary patterns significantly impact the academic performance of children and adolescents. A balanced diet including fruits and vegetables, as well as Mediterranean diet may enhance cognitive function and academic achievements. In addition, a healthy home food environment (HFE), and other factors also play an crucial role in shaping academic performance.